Development of Fire Resistance Plastic Brick - Abdullah, Muhammad Thaufiq (IRC, 2019)
Disposal of plastic waste in environment is a big problem due to its very low biodegradability and presence in large quantities. The purpose of this research is to determine the mechanical properties such as compressive strength and water absorption of composite plastic brick containing variance percentage of recycled plastic bottles and sand.